Contribution Field Industrial Practice About Student Working Readiness Of Machine Engineering Programs Student Working - M Iqbal; Jalius Jama; Refdinal Refdinal (International Journal of Educational Dynamics, 2020)
This research aims to explain the contribution of the readiness of student work Field Industrial practice Vocational High School 1 West Sumatra engineering expertise machining program. The method used is descriptive moetode Ex-post facto or also called measurement after the incident. Subjects in the study were 86iperson who is a student of VHS 1 West Sumatra engineering expertise machining program. Data collection researchers did use a questionnaire that was distributed to the students. Field Industrial practice experience vocational students contributedi32.5% of the students' work readiness. The conclusion of this is the implementation Field Industrial practice peneltiian students of VHS 1 West Sumatra engineering expertise machining program included in both categories, and for job readiness 1 West Sumatra vocational students in the high category. This means that research subjects are students of VHS 1 West Sumatra engineering expertise machining program has a good level of job readiness